2011
DOI: 10.1203/pdr.0b013e3181fcb285
|View full text |Cite
|
Sign up to set email alerts
|

Focal White Matter Abnormalities Related to Neurocognitive Dysfunction: An Objective Diffusion Tensor Imaging Study of Children With Sturge-Weber Syndrome

Abstract: White matter (WM) loss is associated with cognitive impairment in Sturge-Weber syndrome (SWS). In this study, we evaluated if cognitive and fine motor abnormalities are associated with impaired microstructural integrity in specific WM regions in SWS. Fifteen children with unilateral SWS (age: 3-12.4 years) and 11 controls (age: 6-12.8 years) underwent diffusion tensor imaging. Tract Based Spatial Statistics was used for objective comparisons of WM fractional anisotropy (FA) and mean diffusivity (MD) between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
0
24
1
Order By: Relevance
“…Nonetheless, with a clear understanding of the limitations of the technique, it remains evident that DTI is a promising tool that has now become a staple in the investigation of a wide range of neurodevelopmental conditions (Alkonyi et al 2010;Cykowski et al 2010;Filippi et al 2003;Groen et al 2010;Kao et al 2010;Kumar et al 2010;Mullen et al 2010;Radua et al 2010;Shukla et al 2010;Utsunomiya 2010;Wozniak et al 2011b;Yoshida et al 2010). Ultimately, DTI's primary advantage lies in its sensitivity: to neurodevelopmental abnormalities, to normal developmental changes (reviewed below), to changes in disease status including progression and recovery (Teipel et al 2010;Wu et al 2010), and to the effects of both biological and behavioral treatments Keller and Just 2009;Schweder et al 2010;Trivedi et al 2008).…”
Section: A Brief Overview Of Dti Methodsmentioning
confidence: 99%
“…Nonetheless, with a clear understanding of the limitations of the technique, it remains evident that DTI is a promising tool that has now become a staple in the investigation of a wide range of neurodevelopmental conditions (Alkonyi et al 2010;Cykowski et al 2010;Filippi et al 2003;Groen et al 2010;Kao et al 2010;Kumar et al 2010;Mullen et al 2010;Radua et al 2010;Shukla et al 2010;Utsunomiya 2010;Wozniak et al 2011b;Yoshida et al 2010). Ultimately, DTI's primary advantage lies in its sensitivity: to neurodevelopmental abnormalities, to normal developmental changes (reviewed below), to changes in disease status including progression and recovery (Teipel et al 2010;Wu et al 2010), and to the effects of both biological and behavioral treatments Keller and Just 2009;Schweder et al 2010;Trivedi et al 2008).…”
Section: A Brief Overview Of Dti Methodsmentioning
confidence: 99%
“…Our recent studies have also suggested that both grey matter and white matter injury may contribute to Sturge-Weber syndrome related neurocognitive deficits 4,6,9,10 . Early onset white matter damage may lead to disruptions in brain connectivity thus leading to abnormalities that impact the development of intrinsic resting-state brain networks 11,12 (such as default mode, visual, sensory-motor, and language networks), which are present in the human brain both during task performance and rest, across degrees of consciousness.…”
Section: Introductionmentioning
confidence: 89%
“…All three children took antiepileptic drugs (levetiracetam and/or oxcarbazepine) at the time of the evaluation. All three children underwent a neurological examination on the day of the MRI scans, and all three children underwent detailed neuro-psychological or (one year old) developmental and behavioral assessments, as described previously 9,10 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations